ANALISIS PELAKSANAAN TOLERANSI BERAGAMA PADA MAHASISWA PROGRAM STUDI PENDIDIKAN SOSIOLOGI FKIP UNIVERSITAS TANJUNGPURA PONTIANAK - Ade Sambas Pamungkas; Yohanes Bahari; Imran Imran (Universitas Tanjungpura, 2021)
AbstractThis study aims to determine the implementation of tolerance in religious freedom,respect and acceptance of other religions in studentsThe method used is aqualitative method with descriptive analysis. The method used is a qualitativemethod with descriptive analysis. Sources of data in this study are students of theSociology Education Study Program and the data is the result of observations and issupported by the results of interviews with students. The results showed that theimplementation of religious tolerance for students of the Sociology Education StudyProgram, FKIP UNTAN Pontianak, had been carried out well. Found duringobservation and supported by the results of interviews with students. 1) Religiousfreedom for sociology education students is good, as evidenced by the freedom ofeach one to pray according to his religion during observations and interviews withstudents. 2) Respect for other religions is good enough, as evidenced by the mutualrespect and support for other people with different beliefs during observations andinterviews with students. 3) Acceptance of other religions has been proven quite wellwhere students stay in touch and build good relations with friends of other religionsduring observations and interviews with students.Keywords: Religious Tolerance, Students